Determination of atrazine residues in alfalfa plant matrix by ultra-high-performance liquid chromatography and tandem mass spectrometry - Zhu, Yinghui; Rozhkova, T. (Quarantine and plant protection, 2024)
Goal. The purpose of this study was to verify the effectiveness of determination of atrazine residues in alfalfa using ultra-high-performance liquid chromatography and tandem mass spectrometry. Methods. To obtain samples, alfalfa was sprayed once in the field. Plant material was prepared before determination of atrazine residues. For this, the samples (0.2 g) were crushed in liquid nitrogen, 5 ml of water, acetonitrile, and 1% acetic acid were added for extraction. For purification and concentration, 1 mL of supernatant was added to 50 mg of C18, 50 mg of PSA, and 100 mg of anhydrous magnesium sulfate. Chromatography and mass spectrometry conditions: flow rate of 0.4 mL/ min at 40°C was maintained for separation using Agilent, C18 chromatographic columns; detection conditions — desolvation gas temperature and flow 350°C, respectively; nebulizer gas pressure 40.0 psi; ion spray voltage 4500 V; the temperature of the heater MS 1 and MS 2 is 300°C; target compound was quantified using MS/MS acquisition parameters (MRM mode). Results. In the range of 0.01—1.0 mg/L, the mass concentration of atrazine herbicide and the corresponding peak area showed a good linear relationship, with a coefficient of determination of 0.9999. When adding atrazine at 0.1—5.0 mg/ kg, the average value of its content in alfalfa plants was 102.6%—107.5%, and the relative standard deviation was 0.28%—6.85%. The final residue detection result in alfalfa by ultra-high performance liquid chromatography-tandem mass spectrometry was 0.011 mg/kg (the maximum permissible level in China for cereals is 0.05 mg/kg). Conclusions. The method has simple pretreatment operation, high average detection value and precision, good separation and purification effect, short analysis time, and is suitable for the detection of atrazine. It combines two traditional methods into one that is simpler and faster. The sensitivity and reproducibility meet the requirements of general toxicological tests, which have been confirmed by real tests. The method is suitable for the actual needs of detecting herbicide residues in alfalfa samples.